Multiplexed TEM Specimen Preparation and Analysis of Plasmonic Nanoparticles. (30th July 2015) - Mulligan, Sėan K.; Speir, Jeffrey A.; Razinkov, Ivan; Cheng, Anchi; Crum, John; Jain, Tilak; Duggan, Erika; Liu, Er; Nolan, John P.; Carragher, Bridget; Potter, Clinton S.
Abstract: We describe a system for rapidly screening hundreds of nanoparticle samples using transmission electron microscopy (TEM). The system uses a liquid handling robot to place up to 96 individual samples onto a single standard TEM grid at separate locations. The grid is then transferred into the TEM and automated software is used to acquire multiscale images of each sample. The images are then analyzed to extract metrics on the size, shape, and morphology of the nanoparticles. The system has been used to characterize plasmonically active nanomaterials.